Comagmatic Andesite and Dacite in Mount Ijo, Kulonprogo: A Geochemistry Perspective - Irzon, Ronaldo (Pusat Survei Geologi, 2018)
Mount Ijo is a Tertiarry vocano located in Kulonprogo, Yogyakarta Province. Andesite and dacite are the two volcanic rock units in Mount Ijo and around Kulonprogo. Dacite intruded andesite unit in Middle Miocene period. The two volcanic rock units are tried to be correlated based on geochemistry perspective. XRF were applied on major oxides measurements of selected eight samples while ICP-MS on trace and rare earth elements. Major oxides data of volcanic rocks arround Kulonprogo from previous studies are selected for additional data.The studied rocks are classified as basalt, basaltic andesite, andesite, and dacite based on their geochemistry contents. The studied samples show high degree of correlation in the Harker's Diagrams. Olivine and pyroxene fractionation together with ilmenite oxidation are most probably took place along magma differentiation. Alike patterns were also shown both in extended REE and REE spider diagrams. The comagmatic andesite and dacite is evidenced more by constant Rb/Sr ratio escalation through differentiation.Keyword: andesite, dacite, geochemistry, magma differentiation, Kulonprogo